Kombinasi Metode AHP dan TOPSIS dalam Pemilihan Bibit Sayuran Berdasarkan Kondisi Tanah dan Syarat Tumbuh Tanaman - Asep Syaputra (Jurnal Ilmiah Informatika, 2021)
The majority of farmers are still unsure of which vegetable seeds are appropriate for planting on this property. This is due to farmers' lack of understanding of the conditions for planting these vegetable seeds on their fields. Due to farmers' and the general public's lack of understanding of land suitability evaluation, vegetable seeds have not been planted with optimum results because the requirements required for these vegetable crops do not match the land conditions that sustain vegetable growth. Understanding the significance of choosing vegetable seeds based on the adaptability of selecting land and plants also relies solely on farmers' scant knowledge. As a result, the authors believe that more research is needed to decide the best vegetable seeds for cultivation based on soil suitability and plant growth requirements. The AHP approach is very analytical and well-suited to determining the priority weight of each norm, which will later be used as a rating reference by the TOPSIS method. Based on the degree of soil suitability and the conditions for proper growth, it can be calculated that vegetable seeds will be planted later as an alternate, accurate, and dynamic approach